2020
DOI: 10.1186/s12890-020-1098-x
|View full text |Cite
|
Sign up to set email alerts
|

The application of metagenomic next-generation sequencing in diagnosing Chlamydia psittaci pneumonia: a report of five cases

Abstract: Background: Chlamydia psittaci pneumonia is a zoonotic infectious disease caused by Chlamydia psittaci. Diagnostic tools, including culture, serologic test and PCR-based methods, are available but prone to false negative results. Case presentation: This report included five cases of Chlamydia psittaci pneumonia. Symptoms and signs common to all 5 cases included fever, coughing, generalized muscle ache, and most notably, inflammatory infiltration of the lungs upon chest CT and X-ray. Metagenomic next-generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 11 publications
2
59
1
Order By: Relevance
“…11 Studies have shown that mNGS is the most promising comprehensive diagnosis method for infection, especially for severe pneumonia. 12 Recently, several studies have reported the application of mNGS in diagnosing C. psittaci pneumonia, two case reports describing 5 and 9 cases of C. psittaci diagnosed by mNGS 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have shown that mNGS is the most promising comprehensive diagnosis method for infection, especially for severe pneumonia. 12 Recently, several studies have reported the application of mNGS in diagnosing C. psittaci pneumonia, two case reports describing 5 and 9 cases of C. psittaci diagnosed by mNGS 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…In this group, patients complained of neither headache nor muscle soreness, which was inconsistent with results from the previous reports. [ 4 , 5 ]…”
mentioning
confidence: 99%
“…Furthermore, mNGS is less affected by prior antibiotic exposure [12]. Several studies have discussed the potential of mNGS in diagnosing psittacosis or legionnaire's disease [6][7][8]37]. In our study, all 17 psittacosis patients and 9 LP patients were diagnosed with the help of mNGS.…”
Section: Discussionmentioning
confidence: 83%